Gingival enlargement unveiling sarcoidosis: Report of a rare case - Sabeeha Abbas Kadiwala; Mala Baburaj Dixit (Wolters Kluwer Medknow Publications, 2013)
Sarcoidosis is classified as an acquired systemic granulomatous disease. Because of the fact that sarcoidosis affects multiple tissues and organs, it is characterized by many potential signs and symptoms, as well as by the presence of non-caseating granulomas in the organs involved. Although oral sarcoidosis is relatively rare, it may however, present in the oral cavity. This report presents a rare case of sarcoidosis with the initial presenting symptom as severe generalized gingival enlargement. The gingival enlargement was treated by gingivectomy. After histopathological examination of gingival biopsy and certain special investigations, a diagnosis of sarcoidosis was made.